Analysis of Daily Precipitation and Flow Relationship in Büyük Melen Stream (Düzce) - Mücahit Coşkun; Cemil İrdem (Doğal Afetler ve Çevre Dergisi)
This study, it is aimed to analyze the relations between the daily streamflow of Büyük Melen Stream (Düzce) and daily total precipitation and daily precipitation intensity. Considering the importance of Istanbul in meeting the drinking water needs and the potential to create a flood disaster as in 2019, it was found useful to analyze the daily changes in the flow values of the Büyük Melen Stream. Akçakoca daily precipitation data and Uğurluköy streamflow gauge station daily streamflow data were used as data set in the study. The deficiencies in the streamflow data were completed by regression analysis using Beyler streamflow gauge station data. As a method in the study, firstly, the relationships between daily total precipitation and daily flow data were calculated by Pearson correlation analysis. Then, the total daily precipitation was classified as light, normal, moderate, heavy, and very heavy precipitation. Deviation of daily flow values from the previous day for each precipitation intensity class was determined as a percentage. There is a positive correlation between daily total precipitation and flow values in all months for the period average. While the correlation coefficients are highest in January, October, and December with 0.44, the lowest correlation coefficient is in May with 0.15. According to the precipitation intensity classes, the positive effect of the daily total precipitation on the flow was determined as 5.8% for light precipitation, 35.2% for normal precipitation, 66.8% for moderate precipitation, 168.1% for heavy precipitation, and 52.5% for very heavy rains.